(untitled) - Surajit K de Datta (New York, 1981)
This book provides a digest of information about rice research and production. It consists of 14 chapters and at the end of each chapter there is the list of references on where to seek added information
Cây lúa,Thâm cứu sản xuất lúa
Keywords: rice